(untitled) (Nigerian Journal of Technology, 2019)
A study of the property of laterite bricks stabilized with Egg Shell Ash (ESA) and Saw Dust Ash (SDA) in relation to that stabilized with cement was conducted, this was with a view to obtaining an economic replacement for cement. Laterite was stabilized using 0, 2, 4, 8 and 16% (by weight of dry soil) of a mixture of ESA and SDA. The laterite was also stabilized with 5% (by weight of dry soil) of cement to serve as control. For each of these mixes, OMC and MDD of stabilized laterite and compressive strength (qu) of bricks made from stabilized laterite were determined. The results obtained were 47% calcium oxide in ESA, 59.8% silica in SDA, optimum MDD of 1.75 kg/m3, OMC of 19.0% for laterite and optimum of 1.2 N/mm2 for ash stabilized laterite bricks. The optimum results were obtained for ash content of 2 and 4%. The maximum qu obtained for cement stabilized brick was however 2.1 N/mm2. In conclusion, SDA and ESA can be a substitute for cement in low cost housing. http://dx.doi.org/10.4314/njt.v38i2.1